PERANAN ISTRI DALAM PEMENUHAN KEBUTUHAN RUMAH TANGGA NELAYAN DI KALIMANTAN BARAT - Redatin Parwadi (Populasi, 2005)
This study focuses on the life of coastal communities, especially the lives of fishermen's wives in Sungai Raya, Kabupaten Bengkayang, Kalimantan Barat. It attempts to articulate how wives of the fisherfolk manage their time, the kind of work they perform and their contributions to the family income as their efforts to improve the quality of life. There are, however, variations in the patterns of their activities among those whose husbands are traditional independent fishermen and those whose husbands are wage labourers, but using relatively modern technology. The traditional independend fishermen perform more actively to supplement the family income compared to the other one. Working is considered as part of their lives. The side job they do is only to accomodate their spare time, but the money they have from it is not enough to fullfil the family economic.